Comparative Computational Study on Molecular Structure, Electronic and Vibrational Analysis of Vinyl Bromide based on HF and DFT Approach - Ojha, Tulsi; Limbu, Susmita; Shrestha, Prakash Man; Gupta, Suresh Prasad; Rai, Krishna Bahadur (Himalayan Journal of Science and Technology, 2023)
In this study, we have used the Hartree-Fock and Density Functional Theory method of calculation and compared the equilibrium configuration, electronic and vibrational mode of Vinyl Bromide molecule. The molecule is geometrically optimized initially by using 6-31G basis set with B3LYP functional and then bond angles, bond lengths, dihedral angles and IR spectra are compared respectively. Various groups of atoms in Vinyl Bromide molecule by DFT has more accurate bond length, bond angle values rather than by HF computation when comparing with the experimental values. The ground state energies are found at angle 10° or 180° or 360° using HF and DFT method of calculation for the H4-C1-C2-Br6 position. Values of the carbon-hydrogen, carbon-carbon and carbon-bromine bond lengths and bond angles for optimization state of C2H3Br molecule using Hartree-Fock and Density Functional Theory methods with respect to the basis set 6-31G have been analyzed. The C−H in-plane bending vibration and C−H out-of-plane bending vibrations occur in the region 1400–1050 cm-1 and 1000–675 cm-1 respectively. The electronic properties, such as Highest Occupied Molecular Orbital and Lowest Unoccupied Molecular Orbital energies are performed by HF and DFT approach and the difference in Highest Occupied Molecular Orbital and Lowest Unoccupied Molecular Orbital energy gap for HF and DFT method are 14.0847 eV and 6.8994 eV respectively